Students and Teachers' Necessity toward Multimedia Learning Modules (MLMs) Based on Benthik Local Wisdom to Provide Students' Physics Initial Knowledge - Putry, A A; Warsono; Supahar; Jumadi (Journal of physics. Conference series, 2018)
Benthik is one of the local wisdom from DI Yogyakarta that consisted of two stages namely uthat and ilar. Benthik can explain various content of physics through Multimedia Learning Modules (MLMs). This research aims to determine the needs of students and teachers toward MLMs based on benthik local wisdom to provide students' physics initial knowledge. The research used survey method. Data collection instruments used were questionnaires of students needs and interview. Research subjects consisted of 140 senior high school (SHS) students and 3 physics teachers. Research subjects were choosen by purposive sampling. The questionnaires were analyzed by percentage and the result of interview analyzed descriptively. The questionnaire contains about physics learning in schools, physics textbooks used, learning based on local wisdom, the use of technology in learning, and the media needed in learning. The result show that 99,28% of students need or very need MLMs based on benthik local wisdom. This condition is supported by the interview that showed teachers need MLMs because the students prefer to use multimedia technology than textbook. It means that students and teachers need Multimedia Learning Modules (MLMs) based on benthik local wisdom to provide students' physics initial knowledge.